Psychiatric symptoms of progressive supranuclear palsy: a case report and brief review. (February 2014) - Madhusoodanan, Subramoniam; Wilkes, Victoria; Campbell, Rebecca Preston; Serper, Mark; Essuman, Ebenezer Kojo; Brenner, Ronald
SUMMARY The diagnosis of early-stage progressive supranuclear palsy (PSP) can be very confusing. The psychiatric symptoms associated with neurological and medical conditions including PSP are generally not very typical and lead to diagnostic challenges. The symptoms of PSP include vertical gaze palsy, unsteady gait, falls, dysarthria, dementia, apathy, depression, personality changes, disinhibition and psychotic symptoms. In this article we report a patient who had previous diagnosis of Alzheimer's dementia and mood disorder, and presented with hypersexual behavior and mild cognitive symptoms which on closer examination appeared to be associated with PSP. We emphasize the need for awareness of psychiatric presentations of neurological disorders and the importance of obtaining previous medical records from all clinicians.